Proceedings of the National Physics Symposium - National Physics Symposium ( 1988: Universiti of Malaya, Kuala Lumpur); Tan, B. C.; Rasiah, I. J.; Institut Fizik Malaysia (Kuala Lumpur : Institut Fizik Malaysia, 1988)
40